Perempuan Bali dan Kesetaraan Gender dalam Industri Pariwisata - Shantika, Budi (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research aims to raise awareness among industry players and the wider community, especially those working in the tourism industry, regarding gender equality in the Bali tourism industry. Research methods: The research methodology employed is a literature review. Analysis of textual descriptions was carried out using the Gender Equality Continuum Assessment concept. Results and discussion: The findings reveal injustices faced by Balinese women working in the tourism sector, including the perpetuation of stereotypes implying limitations in managing the tourism sector and inadequate legal protections. These findings underscore the necessity of raising public awareness about gender inequality and enforcing legal protections for women in the tourism sector. Implications: By implementing gender equality policies and raising awareness of gender roles, the tourism industry is expected to create a more inclusive and fair environment thereby promoting social justice and fostering economic development.